2022
DOI: 10.2196/30230
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Mobile Health and Social Media–Based Interventions for Young Adults With Early Psychosis and Clinical Risk for Psychosis: Survey Study

Abstract: Background Digital technology, the internet, and social media are increasingly investigated as promising means for monitoring symptoms and delivering mental health treatment. These apps and interventions have demonstrated preliminary acceptability and feasibility, but previous reports suggest that access to technology may still be limited among individuals with psychotic disorders relative to the general population. Objective We evaluated and compared a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…34,45 The potential of technologybased interventions as an alternative to in-person interventions has been documented. 46 Whether this translates to Nearly half of the participants indicated their preferred primary goal for a harm reduction intervention as reducing use, rather than using cannabis in less harmful ways or avoiding risky cannabis-related situations. It is worth noting that half of our sample had a CUD but did not want CUD treatment, instead preferring harm reduction interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,45 The potential of technologybased interventions as an alternative to in-person interventions has been documented. 46 Whether this translates to Nearly half of the participants indicated their preferred primary goal for a harm reduction intervention as reducing use, rather than using cannabis in less harmful ways or avoiding risky cannabis-related situations. It is worth noting that half of our sample had a CUD but did not want CUD treatment, instead preferring harm reduction interventions.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 45 The potential of technology-based interventions as an alternative to in-person interventions has been documented. 46 Whether this translates to intervention adherence or efficiency remains to be studied. Considering the scarcity of cannabis-specific interventions, the challenge of engagement, and the potential for technology-based interventions to enhance well-being in individuals with EP, 47 developing cannabis-focused, technology-based interventions offer an opportunity to enhance health services.…”
Section: Discussionmentioning
confidence: 99%
“…During this selection phase, any disagreements among the investigators were resolved by discussion and consultation with a reviewer who was not actively involved in the study selection. The quality assessment for each studied was assessed using the tool of the National Heart, Lung, and Blood Institute (NIH) (https://www.nhlbi.nih.gov/health-topics/studyquality-assessment-tools) for cross-sectional studies that included 14 criteria (29). Two independent researchers assessed each article.…”
Section: Data Collectionmentioning
confidence: 99%
“…Patients with FEP have high rates of technology ownership and use as evidenced by a 2022 study of an FEP clinic that found that patients’ access to smartphones was 100% and that 66% of the patients used social media [ 4 ]. A variety of new technologies have been studied in CSC including apps, web-based videos, games, and social media platforms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%